Difficulties of Venezuelan migrants in the context of the Covid19 pandemic in Ecuador - Moreira Molina, Karla Lorena (2021)
The problems derived from Venezuelan migration have increased in the Ecuadorian scenario, after the declaration of a state of emergency by Covid-19. During this period, several non-governmental organizations (NGOs), which it organizes in the city of Manta, focused their activity on the distribution of humanitarian aid to satisfy basic needs of this group under pressure. The present work sought to recognize the incidence and repercussion of the ignorance that migrants have on the workforce developed by NGOs. Variables such as the regularization of immigration status, knowledge and fulfillment of rights and obligations, as well as the processes of dissemination of social and legal services are explored. The process of data collection and analysis will be seen from a mixed research perspective, with the application of a survey questionnaire applied to 391 participants, and several interviews with key actors. The results show the recruitment of difficulties during the pandemic, and the fact that a large part of the community of Venezuelans residing in Manta have not been benefited by humanitarian aid, nor by other social and legal services.